2017
DOI: 10.18632/oncotarget.16130
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the genomic landscape in Waldenström's Macroglobulinemia for targeted therapeutical interventions

Abstract: The Literature has recently reported on the importance of genomics in the field of hematologic malignancies, including B-cell lymphoproliferative disorders such as Waldenström's Macrolgobulinemia (WM). Particularly, whole exome sequencing has led to the identification of the MYD88L265P and CXCR4C1013G somatic variants in WM, occurring in about 90% and 30% of the patients, respectively. Subsequently, functional studies have demonstrated their functional role in supporting WM pathogenesis and disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, these studies highlight the importance of understanding both MYD88 and CXCR4 mutation statuses in LPL/WM and may provide the basis for a more personalized treatment approach. Nowadays, targeting CXCR4 represents an innovative, interesting therapeutic approach in patients with WM, either harboring or not harboring the CXCR4 WHIM mutation [160]. In addition to plerixafor, several other antagonists to CXCR4 have been developed and are in clinical trials, including uloclupumab, mavorixafor, and burixafor (TG-0054), and could be investigated for use either alone or in combination treatment strategies for LPL/WM patients with CXCR4 mutations.…”
Section: Cxcr4 Whim-like Mutations In Lpl/wmmentioning
confidence: 99%
“…However, these studies highlight the importance of understanding both MYD88 and CXCR4 mutation statuses in LPL/WM and may provide the basis for a more personalized treatment approach. Nowadays, targeting CXCR4 represents an innovative, interesting therapeutic approach in patients with WM, either harboring or not harboring the CXCR4 WHIM mutation [160]. In addition to plerixafor, several other antagonists to CXCR4 have been developed and are in clinical trials, including uloclupumab, mavorixafor, and burixafor (TG-0054), and could be investigated for use either alone or in combination treatment strategies for LPL/WM patients with CXCR4 mutations.…”
Section: Cxcr4 Whim-like Mutations In Lpl/wmmentioning
confidence: 99%
“…A very rich literature compared gene expression profiles in tissues collected from healthy and cancer donors to identify the transcriptomic signatures of various cancer phenotypes (e.g., references [1,2,3,4,5]) that are periodically organized in the atlas form (e.g., references [6,7]). Nanostring launched recently a panel claiming to categorize the disease heterogeneity using 32 biological signatures involving 770 genes across 23 key breast cancer pathways ().…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent activating somatic mutations (frameshift or nonsense) are also found in C–X–C chemokine receptor type 4 ( CXCR4 ) gene in a frequency of about 30–40% of patients with WM and less often in those with IgM MGUS, representing the second most mutated gene in WM [ 2 , 3 , 12 ]. CXCR4 is a G-protein-coupled receptor, acting as a key regulator of cell trafficking in heamatopoietic stem cells and clonal B cells, also interacting with the related ligand stromal-derived factor 1 [ 13 16 ]. Studies have shown the relevance of specific CXCR4 mutations to enhanced WM cell dissemination leading to in vivo disease progression as well as increased resistance to ibrutinib treatment [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%